Transitioning to Online Learning amid COVID-19: Perspectives in a Civil Engineering Program - Maraqa, Munjed A.; Hamouda, Mohamed; El-Hassan, Hilal; El Dieb, Amr S.; Aly Hassan, Ashraf (Online Learning, 2022)
The transition from face-to-face classes to fully online learning (OL) during the spring semester of 2020 occurred almost globally because of the imposed COVID-19 lockdown. The present study investigated the perception and experiences of undergraduate students and faculty members of the Civil Engineering program at the United Arab Emirates University concerning switching to OL during COVID-19. Quantitative questionnaires were distributed to faculty members and students following the end of the spring semester of 2020. Students and faculty members identified student engagement and online exams as major areas that require improvement. Online exams were challenging for students and difficult to prepare, control, and administer for faculty. Providing technical support is critical for the successful streaming of online courses. Initially, half of the surveyed students began the transition with a positive attitude toward OL, and this percentage increased during the transition. The capacity to continue learning during the COVID-19 crisis and the availability of recorded materials were perceived by the students as the main advantages of OL while challenging online examinations and the lack of social interaction were the main disadvantages.